2021
DOI: 10.1161/circulationaha.121.056038
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Evaluation of a Case of Presumed Myocarditis After the Second Dose of COVID-19 mRNA Vaccine

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 38 publications
5
115
1
Order By: Relevance
“…Anaphylaxis after COVID-19 mRNA vaccination has been observed more commonly than the estimated 1 to 2 cases per million doses reported after receipt of influenza vaccine and some other vaccines. 25 Estimated anaphylaxis incidence rates after receipt of both BNT162b2 and mRNA-1273 vaccines in this study were similar to rates after receipt of mRNA vaccines in other reports, 21,26 although somewhat higher than VAERS estimated reporting rates. 27 In contrast, estimated anaphylaxis incidence rates were much lower than the 24.7 cases of con-firmed anaphylaxis per 100 000 vaccinees estimated through prospective surveillance of health care workers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Anaphylaxis after COVID-19 mRNA vaccination has been observed more commonly than the estimated 1 to 2 cases per million doses reported after receipt of influenza vaccine and some other vaccines. 25 Estimated anaphylaxis incidence rates after receipt of both BNT162b2 and mRNA-1273 vaccines in this study were similar to rates after receipt of mRNA vaccines in other reports, 21,26 although somewhat higher than VAERS estimated reporting rates. 27 In contrast, estimated anaphylaxis incidence rates were much lower than the 24.7 cases of con-firmed anaphylaxis per 100 000 vaccinees estimated through prospective surveillance of health care workers.…”
Section: Discussionsupporting
confidence: 82%
“…This current surveillance complements other vaccine safety monitoring systems in the US, including the Vaccine Adverse Event Reporting System (VAERS) and v-safe. 21 Key strengths of this surveillance are that it is population based, geographically diverse, and updated weekly. Outcome incidence among vaccinees in a risk interval was compared with outcome incidence among similar vaccinees who were in their comparison interval on the same calendar date.…”
Section: Discussionmentioning
confidence: 99%
“…Other hypothesized mechanisms include induction of anti-idiotype cross-reactive antibody-mediated cytokine expression in the myocardium and the aberrant induction of apoptosis and results in inflammation of myocardium and pericardium. Furthermore, Muthukumar et al conducted detailed immunologic investigation in a 52-year-old man who developed myocarditis three days after receiving the second dose of Moderna mRNA COVID-19 vaccine and found that his antibody responses to 18 different SARS-CoV-2 antigens did not differ (and was lower for some antigens) from vaccinated controls who did not develop complications [22]. The mRNA vaccines can also induce a non-specific innate inflammatory response or a molecular mimicry mechanism between the viral spike protein and an unknown cardiac protein [23].…”
Section: Causal Relation Between Mrna Vaccine and Myocarditis/pericarditismentioning
confidence: 99%
“…Similarly, the European Medicines Agency (EMA) reports less than a thousand cases of myopericarditis up to June 2021 2 . The cases described in literature usually present with fever, chest pain, and dyspnea, together with changes on the electrocardiogram and cardiac magnetic resonance findings consistent with myocarditis; the symptoms usually resolved rapidly (114)(115)(116)(117)(118)(119)(120). The patients were treated with non-steroidal anti-inflammatory drugs (NSAIDs) only, but, in some cases, required intravenous immune globulin (IVIG) and corticosteroids (114)(115)(116)(117)(118)(119)(120).…”
Section: Cardiovascular Involvement After Covid-19 Vaccinationmentioning
confidence: 99%
“…The cases described in literature usually present with fever, chest pain, and dyspnea, together with changes on the electrocardiogram and cardiac magnetic resonance findings consistent with myocarditis; the symptoms usually resolved rapidly (114)(115)(116)(117)(118)(119)(120). The patients were treated with non-steroidal anti-inflammatory drugs (NSAIDs) only, but, in some cases, required intravenous immune globulin (IVIG) and corticosteroids (114)(115)(116)(117)(118)(119)(120). However, up-to-date, no causal relationship between vaccine administration and myocarditis has been established.…”
Section: Cardiovascular Involvement After Covid-19 Vaccinationmentioning
confidence: 99%